2010
DOI: 10.1016/j.envres.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Mercury exposure, serum antinuclear/antinucleolar antibodies, and serum cytokine levels in mining populations in Amazonian Brazil: A cross-sectional study

Abstract: Mercury is an immunotoxic substance that has been shown to induce autoimmune disease in rodent models, characterized by lymphoproliferation, overproduction of immunoglobulin (IgG and IgE), and high circulating levels of autoantibodies directed at antigens located in the nucleus (anti-nuclear autoantibodies, or ANA) or the nucleolus (anti-nucleolar autoantibodies, or ANoA). We have reported elevated levels of ANA and ANoA in human populations exposed to mercury in artisanal gold mining, though other confounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
4
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 73 publications
8
119
4
5
Order By: Relevance
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. In a retrospective cross-sectional study from the same group Gardner and coworkers (Gardner et al, 2010) confirmed the results of Silva et al (2004). They found a higher prevalence of serum antinuclear (ANA) and antinucleolar (ANoA) antibodies in gold miners exposed to mercury, as compared with workers employed in other minerals mining with non-occupational exposure to mercury.…”
Section: Immunotoxicitysupporting
confidence: 69%
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. In a retrospective cross-sectional study from the same group Gardner and coworkers (Gardner et al, 2010) confirmed the results of Silva et al (2004). They found a higher prevalence of serum antinuclear (ANA) and antinucleolar (ANoA) antibodies in gold miners exposed to mercury, as compared with workers employed in other minerals mining with non-occupational exposure to mercury.…”
Section: Immunotoxicitysupporting
confidence: 69%
“…Large and uncontrolled production of infl ammatory cytokines plays a key role in aetiology and development of autoimmune diseases (Hu et al, 1999). Also it can alter the host-pathogen interactions or increase the susceptibility to diseases (Gardner et al, 2010). Hemdan et al (2007) in vitro demonstrated differences in Hg effect on the Th1/Th2 balance after different cells stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68][69] Mercury-exposed gold miners in Brazil were found to have higher levels of ANA antibodies compared with non-mercury miners, suggesting that mercury exposure can lead to antibody responses that are characteristic of autoimmunity. 70 Further, Dr. Monestier described divergent effects between female and male mice offspring following postnatal exposure of the mother to mercury, with female offspring exhibiting a decrease in regulatory T cells. He further stated that the biodistribution, toxiocokinetics, and mercury accumulation differ between the sexes, though this research area remains largely unexplored.…”
Section: Chemical Exposuresmentioning
confidence: 99%